INVESTIGATING THE RELATIONSHIP BETWEEN ACTIVE LEADERSHIP AND CONSTRUCTION RISK MANAGEMENT AMONG CONTRACTORS IN KINGDOM OF SAUDI ARABIA - Muhammad Abdul Rehman,; Md Sayuti Bin Ishak, (Journal of Surveying, Construction and Property, 2022)
Contractors have given importance to risks in the construction process as it causes time and cost overrun, delays and total desertion in activities and events present in the construction project. The uncertainty in the completion time, cost and quality during construction relates to construction risks. One important factor to deal with construction project complexities is active leadership. Present research examines the significant relation of active leadership on construction risk management associated with contractors working in Kingdom of Saudi Arabia (KSA). Based on Organization Control theory, current research (quantitative in nature) discusses the influence of active leadership on construction risk management with the moderation role of government acts, laws and policies among 303 big size company (> 250 number of employees) contractors working in Kingdom of Saudi Arabia (KSA) using PLS-SEM technique. Survey questionnaires were distributed with valid response rate of 82% using 5 point Likert scale. PLS-SEM is a composite based approach, which provides parameter estimation with high efficiency and increased statistical power for analyzing complex models. It is a causal-predictive method approach in which data distribution assumption is not taken into account for estimation of complex models which contains various constructs with variable indicators and structural paths. Results depict that government acts, laws and policies and active leadership positively influence construction risk management. In addition, moderation of government acts, laws and policies has positive relation among active leadership and construction risk management. It is difficult to control power in term of risk occurrence and low practice of government acts, laws and policies results high level of risk occurrence reducing efficiency of delivery output resulting construction risk management less effective. The reduction in risk occurrence during construction phase of project is supported by active leadership with lengthening the theory by inspecting extensive construction project risk ranges which includes equipment and labor risk, finance risk, design risk, material risk and administrative or management risk making organization effective. Organizational management can reduce risk occurrence within project by building conditions for enhancing active leadership among their employees.